ANALISIS PERGERAKAN MAGMA GUNUNG MERAPI DENGAN MENGGUNAKAN DIAGRAM SERTA ESTIMASI POTENSI VOLUME MAGMA DENGAN MENGGUNAKAN DATA GRAVITASI - , APRILIA NURMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was using gravity and elevation data of Merapi Volcano during August 1998 â August 2000. The data were gathered from 11 benchmarks which were spread around the summit of the volcano. The data were calculated and analyzed using diagrams. The Free-Air Gradient is -308.6 Î¼Gal, using assumption that the density of the magma is 2400 kg/m3. Then, value at each data point was plotted into diagram. Magma movement estimation was done by analyzing diagrams. The result shows that each period of measurement exhibit the same pattern of magma movement which is moving from south-south east and north west towards the summit of Merapi Volcano. Volume calculation has been done to find out the accumulation of material that would be erupted. Gravity changes is used for calculating mass changes based on Gauss Theorem. The result of 1-year-measurement period was 0.98 million m3 of potential volume, while the 2-year-measurement period was 0,61 million m3. Compared to the real volume of lava dome which formed at 2001, which is 1 million m3, the 1-year-measurement is considered to be more accurate.